2021
DOI: 10.1007/s00264-021-05116-z
|View full text |Cite
|
Sign up to set email alerts
|

Bony callus stiffness indirectly evaluated by the axial load-share ratio in vivo as a guide to removing a monolateral external fixator safely

Abstract: Purpose As the monolateral external fixator is increasingly used in trauma-control and definitive management for high-energy long bone fractures, timing the fixator removal remains a challenge for surgeons. The purpose of this study was to determine the feasibility and effectiveness of the bony callus stiffness indirectly evaluated by the axial load-share ratio in vivo as a guide to removing a monolateral external fixator safely. Methods A total of 131 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…According to Krettek C et al [ 29 ], the refracture ratio after fixator removal was 6%. Liu et al [ 6 ] reported 52 cases of tibial fractures treated by external fixation, in which 4 patients suffered refracture following the fixator removal, with a refracture ratio of 7.7%. Therefore, timing fixator removal is an essential decision for a satisfactory outcome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Krettek C et al [ 29 ], the refracture ratio after fixator removal was 6%. Liu et al [ 6 ] reported 52 cases of tibial fractures treated by external fixation, in which 4 patients suffered refracture following the fixator removal, with a refracture ratio of 7.7%. Therefore, timing fixator removal is an essential decision for a satisfactory outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring axial stiffness provides a more direct approach to assessing the load-bearing capacity of the affected limb. Several studies [ 3 , 6 , 18 , 19 ] have demonstrated that LS measurement is an effective method for evaluating the axial stiffness of the callus in vivo. This method works upon the principle that an externally applied compressive load distributes between the fixator and the bone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, in vivo monitoring technology has emerged, mainly focusing on the changes in mechanical parameters with time during the mineralization of new tissues [ 80 83 ]. Liu and Aarnes et al [ 84 , 85 ] proposed that the axial load sharing ratio can be used to indirectly evaluate the hardness of calluses as the basis for safe removal of external fixators. Mora Macias et al [ 82 ] also proposed a new distractor that can detect the axial stiffness of calluses.…”
Section: Introductionmentioning
confidence: 99%